1996
DOI: 10.1002/(sici)1097-4628(19961010)62:2<319::aid-app7>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry and photoinitiation activity of radical polymerization of 2‐substituted anthraquinone derivatives. III. Nanosecond laser flash photolysis study

Abstract: Plas Coch, Wrexham, Clwyd L11 2AW, U.K.; and 31nstituto de Ciencia y Tecnologia de Polimeros, C.S.I.C., c/]uan de la Cierva 3, 28006 Madrid, Spain SYNOPSIS A nanosecond laser Hash photolysis study was undertaken on a selected range of 2-substituted anthraquinone derivatives and the data are discussed in relation t o the photoactivities in industrial photopolymerization. All the compounds give rise to a triplet-triplet absorption t h a t is quenched by ground-state molecular oxygen. T h e transient half-lives r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 11 publications
4
11
0
Order By: Relevance
“…Therefore, this makes it less photochemically reactive. This fact is also in agreement with much of our previous reported studies [1][2][3][4][5][6][7][8]. We found that many 2-substituted anthraquinones exhibited a longest wavelength absorption maximum at between 330-360nm with a small and variable shift.…”
Section: Spectroscopic Study On the 2 Substituted Methylanthraquinonessupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, this makes it less photochemically reactive. This fact is also in agreement with much of our previous reported studies [1][2][3][4][5][6][7][8]. We found that many 2-substituted anthraquinones exhibited a longest wavelength absorption maximum at between 330-360nm with a small and variable shift.…”
Section: Spectroscopic Study On the 2 Substituted Methylanthraquinonessupporting
confidence: 93%
“…The photophysical and photochemical properties of anthraquinone derivatives has been one of the main areas of study in our research investigating the relationship and understanding between molecular structure, excited state properties and light stability and photochemical activity [1][2][3][4][5][6][7][8]. They have many applications in dye and pigmentbased, water and oil miscible, acrylated matrices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data come from the development of a standard for instrument calibration by NIST to improve the accuracy of measurements by application of nonlinear liquid standards. 4 Figure 11.2 shows the effect of polymer concentration on the viscosity of a solution of polyphenylene in N-methyl pyrilidinone. 5 Two regimes are clearly visible.…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…Work on anthraquinone derivatives, which are common photosensitizers, has shown that when photosensitizer is dissolved in isopropanol (hydrogen-donating solvent) the half-life of radicals is increased by a factor of seven compared to acetonitrile (a non-hydrogen-donating solvent). 4 This shows that the ability of a photosensitizer to act in this manner depends on the presence of a hydrogen donor (frequently the solvent). In studies on another group of photosensitizers  1,2-diketones, the solvent cyclohexane increased the absorption wavelength of the sensitizer in the UV range by more than 10 nm compared with solutions in ethanol and chloroform.…”
Section: Other Properties Affected By Solventsmentioning
confidence: 99%